Ethics of Buying and Selling Online Sharia Economic Perspective: Study of the Concept of Iqâlah - Nurul Hakim; Barakat Muhammad Ahmad Muhammad Hamad Al-Nil; Mahmoud Saleh Mubarak Bin Humaid (Demak Universal Journal of Islam and Sharia, 2023)
This study aims to analyze the hadith regarding Iqâlah or cancellation of trading transactions, especially in online platforms. In addition, this theme is also side by side with the discussion of khiyâr, or the right to choose between buying and selling which is part of the ethics of sharia trading. The other goal is to be able to provide a right understanding of the concept and law of Iqâlah to the performers in economic activity by analyzing related hadiths and the concept of khiyâr, thereby minimizing the occurrence of harm and losses due to the cancellation of trading transactions that are not by the rules and norms of Shari'a. The methodology used in this research is qualitative, in the form of literature research by analyzing related data as reading materials. In this study, the authors found that Iqâlah is permissible and even some scholars say that the law is Sunnah. In addition, there must be an understanding between the seller and the buyer regarding the correct concept of Iqâlah and Khiyâr so that benefit is achieved between the two parties. The results of the study show that Iqâlah is permissible as long as it is based on the normative values ​​of the Koran and Sunnah and can be considered an act of breaking a promise if it is done unilaterally and does not comply with the ethics of shariah trading.